Menyingkap Feminisme Perspektif Akuntansi Islam - Ahmad Fahrudin Alamsyah (el Harakah: Jurnal Budaya Islam, 2001)
Modern culture is actually dominated by masculine traits, such as material life, expansive rational, exploitative, competitive, egoistic, quantitative, and so on. Femininity will give a place to masculinity to power while femininity is behind. This is evident from the existence of a comparative study between mainstream accounting and Shari'ah accounting, in an attempt to expose the Ah-Shari'ah feminism that has been marginalized. This paper discusses Islamic accounting perspective as a new paradigm. The essence of Islamic accounting is essentially an attempt to deconstruct modern accounting into a more humanist and value-packed form. Shari'ah accounting is a new technology that shows that social, moral, and spiritual values are an important concern in determining the principles to be developed. Therefore, the concept of accountability in shari'a accounting is more emphasis on two mutually balanced sides of the concept of responsibility in the context of Hamblum minallah and Hamblum minannas. In the first concept is a form of manifestation of worship, which relates between human beings as being with Al-lah as-the Creator. While the second refers more to the existence of human beings as social beings. This form of accountability is manifested in the objectives of shari'ah accounting. Budaya modern sebetulnya didominasi oleh sifat maskulin, seperti kehidupan yang material, rasional ekspansif, eksploitatif, kompetitif, egois, kuantitatif, dan sebagainya. Femininitas akan memberikan tempat kepada maskulinitas untuk berkuasa sementara femininitas berada di belakang. Hal ini tampak dari adanya suatu studi komparatif antara akuntansi mainstream dengan akuntansi Syari’ah, sebagai upaya untuk menyingkap feminisme Ah-Syari’ah yang selama ini terpinggirkan. Tulisan ini membahas perspektif akuntansi Islam sebagai paradigma baru. Esensi dari akuntansi Islam pada dasarnya merupakan sebuah upaya mendekonstruksi akuntansi modem ke dalam bentuk yang lebih humanis dan sarat nilai. Akuntansi syari’ah merupakan suatu teknologi baru yang menunjukkan bahwa nilai sosial, moral, dan spiritual menjadi suatu perhatian penting dalam penetapan prinsip-prinsip yang akan dikembangkan. Oleh karena itu konsep akuntabilitas pada akuntansi syari’ah lebih menekankan pada dua sisi yang saling berimbang yakni konsep pertanggunggungjawaban dalam konteks Hamblum minallah dan Hamblum minannas. Pada konsep pertama merupakan bentuk manifestasi dari ibadah, yang berhubungan antara manusia sebagai mahluk dengan Allah sebagai-Sang Pencipta. Sedangkan yang kedua lebih mengacu pada eksistensi manusia sebagai mahluk sosial. Bentuk akuntabilitas tersebut dimanifestasikan dalam tujuan akuntansi syari’ah.